"For Their Own Good": A Response to Popular Arguments Against Permitting Medical Assistance in Dying (MAID) where Mental Illness Is the Sole Underlying Condition. (July 2018) - Dembo, Justine; Schuklenk, Udo; Reggler, Jonathan
Canada is approaching its federal government's review of whether patients should be eligible for medical assistance in dying (MAID) where mental illness is the sole underlying medical condition, and when "natural death" is not "reasonably foreseeable". For those opposed, arguments involve the following themes: capacity, value of life, vulnerability, stigma, irremediability, and the role of physicians. It has also been suggested that those who are able-bodied should have to kill themselves, even though suicide may be painful, lonely, and violent. Opponents of MAID for severe, refractory suffering due to mental illness imply that it is acceptable to remove agency from such patients on paternalistic grounds. After years of efforts to destigmatise mental illness, these kinds of arguments effectively declare all patients with mental illness, regardless of capacity, unable to make considered choices for themselves. The current paper argues that decisions about capacity must be made on an individual-patient basis. Given the rightful importance granted to respect for patient autonomy in liberal democracies, the wholesale removal of agency advocated by opponents of a permissive MAID regime is difficult to reconcile with Canadian constitutional values.